Assessment of General Characteristics of Geriatric Patients Admitted in a Tertiary Care Teaching Hospital - Palani, Thennarasu; V Trichur, Ramakrishnan; Kurian, Selina Grace; M, Selvabharathi; M, Sivashankari; AS, Shalini; Jeyabalan, Srikanth (Journal of Pharmacy Practice and Community Medicine)
Aim/Background: The study aims to identify the risk profile of patients aged above 65 years and to study the pattern of drug use and resource planning for interventions. Methods and Materials: A prospective observational study was conducted in the Department of Emergency and Critical Care, Sri Ramachandra Institute of Higher education and Research that offers health care services in Porur, Chennai. Eighty-four patients were watched during the study period of 6 months. After providing written and oral information, written informed consent or proxy content was obtained from every participant before inclusion. Results: We characterized adults older than 65 years attending the ED in urban tertiary health care teaching hospital and observed several parameters like demographic variables, admission and discharge details, Prolonged Length of Stay (LOS), reasons for admission to Emergency Department, diagnosis, comorbidities, polypharmacy and final disposition. Conclusion: The rate of hospitalization and the rate of admissions were higher for the geriatric population when compared to younger adults in the Emergency Department. These rates increased with increasing age, presence of comorbidities and acute illness severity. In our study, disorders of the circulatory system were the leading cause that led to admission, hospitalization and mortality of the elderly.
Keywords: Prospective; Observational study; Risk profile; Drug use; Comorbidity; Hospitalization.